2008
DOI: 10.1080/14786430802464248
|View full text |Cite
|
Sign up to set email alerts
|

Small-scale gravitational instabilities under the oceans: Implications for the evolution of oceanic lithosphere and its expression in geophysical observables

Abstract: Sublithospheric small-scale convection (SSC) is thought to be responsible for the flattening of the seafloor depth and surface heat flow observed in mature plates. Although the existence of SSC is generally accepted, its ability to effectively produce a constant lithospheric thickness (i.e. flattening of observables) is a matter of debate. Here we study the development and evolution of SSC with a 2D thermomechanical finite-element code. Emphasis is put on (i) the influence of various rheological and thermophys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 57 publications
5
27
1
Order By: Relevance
“…[11] Previous studies have demonstrated the important role of radiogenic heat production in controlling the thermal thickness of OL and the cooling of the sublithospheric upper mantle by SSC [e.g., Jarvis and Peltier, 1980;Huang and Zhong, 2005;Zlotnik et al, 2008], and therefore we do not address this point here. We note, however, that all our simulations include a realistic radiogenic heat production value of 1.8 Â 10 À8 W m À3 [Labrosse and Jaupart, 2007].…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…[11] Previous studies have demonstrated the important role of radiogenic heat production in controlling the thermal thickness of OL and the cooling of the sublithospheric upper mantle by SSC [e.g., Jarvis and Peltier, 1980;Huang and Zhong, 2005;Zlotnik et al, 2008], and therefore we do not address this point here. We note, however, that all our simulations include a realistic radiogenic heat production value of 1.8 Â 10 À8 W m À3 [Labrosse and Jaupart, 2007].…”
Section: Resultsmentioning
confidence: 95%
“…Neglecting this term increases the density difference between upwellings and downwellings, and consequently the vigour and eroding capacity of SSC (Figure 2c). This may result in underestimations of the steady-state thermal thickness of OL by as much as 25-50 km [see also Zlotnik et al, 2008].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The base of the lithosphere (i.e., conduction‐dominated layer) is identified as the 1250°C isotherm. This is consistent with numerical simulations of small‐scale convection with realistic viscosities [e.g., Zlotnik et al ., ; Afonso et al ., ; Ballmer et al ., ] indicating that isotherms above ~1250°C tend to be dominated by advection. The sublithospheric thermal structure is obtained by linear interpolation between (inverted) values of the main nodes T buffer , T inter , and T bottom (Figure ).…”
Section: Model and Methodsmentioning
confidence: 98%